Teaching macroeconomics after the crisis - Peter Bofinger (University of Würzburg, Department of Economics, 2011)
It is often said that after the crisis economic textbooks have to be rewritten. However, as surveys show, almost all professors continue using the standard IS-LM/AS-AD model as the workhorse for undergraduate training. This paper shows that the IS-LM/AS-AD model is not only full of obvious inconsistencies, e.g. using two aggregate demand and two aggregate supply curves, it also presents the economy as an inherently stable system which is only destabilized by wage rigidities and policy shocks. Thus, it cannot explain involuntary unemployment and it pretends that deflation is a self-stabilizing mechanism if an economy is affected by a negative demand shock. This paper shows that it is relatively easy to reinterpret the basic model in a way that inconsistencies can be avoided and the inherent instability of macroeconomic processes which underlies the Keynesian paradigm can be demonstrated. It also allows a discussion of monetary policy in a more topical way than the traditional LM-curve.
Keywords: A10; A11; A22; E12; 330; Keynesian economics; AS/AD model; economic crisis; cyclical unemployment; Wirtschaftsstudium; IS-LM-Diagramm; Keynesianismus; Wirtschaftskrise; Konjunkturelle Arbeitslosigkeit